Apakah Theory Planned of Behaviour Dapat Mempengaruhi Perilaku Academic Fraud? Can The Theory Planned of Behavior Affect Academic Fraud Behavior? - Biduri, Sarwenda (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this research is (1) to analyze the impact on interest behave (2) to analyze is a subjective influences interest behave (3) do control behavior perceived influences interest behave (4) is a moral obligation influences interest behavior (5) do interest behave influences behavior student academic dishonesty . This research uses the quantitative with the survey through the questionnaire and it will be distributed in stiesia, university wijaya kusuma, university trunojoyo, muhammadiyah university sidoarjo.This research using two types of variables, the independent variable and variable dependen.variabel independent is the type variables explain or affect other variables, namely kontruk attitude, subjective norm, control behavior that perceived and moral obligation.The testing of hypotheses in this research use some help software Smart PLS. The result of this research is a moral obligation significant to academic interest, control the significant to academic interest, a norm subjective do not affect significant impact on academic interest, and interest academic significant to behavior dishonesty academic.